Application of combined space, arial and ground based multiple technologies in deformation monitoring of mining areas - Huihui JIA; Jianzhi XUE; Lizhao GUO; Jiangtao SONG; Yucong ZHANG (Zhongguo dizhi zaihai yu fangzhi xuebao, 2023)
There are a large number of iron mine gobs due to many years of mining in Zhoutaizi Village, Zhangbaiwan Town, Luanping County. And some gobs have potential safety hazards of collapse, which seriously restrict the local economic development and social stability. So it is necessary to strengthen deformation investigation and field monitoring of existing gobs in this area. In this paper, the spatial distribution of gobs in the study area is determined and deformation of gobs is monitored by using Interferometric Synthetic Aperture Radar (InSAR), UAV photogrammetry and 3D laser scanning technology. Firstly, Small Baseline Subset InSAR (SBAS-InSAR) technology is used to retrieve the surface deformation of gobs. Then, a three-dimensional model of the study area is constructed by using UAV data, and the ground surface changes between two flights are calculated by using multi-period UAV flight data to support the results of InSAR technology. Finally, 3D laser scanning technology is applied to some areas, and the fine model of gobs is established. The results show that the joint monitoring results of the three technologies show a high consistency, the maximum deformation rate (−25 mm/a) of the study area are detected by InSAR method. Combined with the difference results of the DEM and 3D laser scanning data of the two periods of UAV, 17 high-risk areas of gobs are identified. The high-risk areas are distributed in various mining areas, and some areas have an impact on residential areas and roads. The based on Space, Sky and Ground multi-technology indicating that this method has high reliability and can be well applied to deformation investigation of goaf in mining area and the surface deformation monitoring during inadequate mining.